2013
DOI: 10.2319/110412-849.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chinese and white Bolton standards at age 13

Abstract: Objectives: To create a combined male-female Chinese Bolton standard for age 13 and to compare it to the combined Bolton standard for white 13 year olds. Materials and Methods: Thirty-two Chinese and 32 white subjects (16 adolescent boys and 16 adolescent girls aged 13 years in each ethnic group) who fulfilled the selection criteria used to create the original Bolton standards were enrolled. Their cephalograms were traced and then averaged two at a time following the Bolton method. In addition to creating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The applicability of this normative data to other ethnic populations has been questioned in numerous studies. [33][34][35][36] As a result, this normative data is not an appropriate control group for our heterogeneous population. Instead, we utilized measurements of patients undergoing open resection as a control group, isolating effects of the EEA on midfacial development by including only patients with craniopharyngioma on final pathology and postoperative panhypopituitarism in addition to adjusting for sex, age at presentation, and duration of imaging follow-up in our statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The applicability of this normative data to other ethnic populations has been questioned in numerous studies. [33][34][35][36] As a result, this normative data is not an appropriate control group for our heterogeneous population. Instead, we utilized measurements of patients undergoing open resection as a control group, isolating effects of the EEA on midfacial development by including only patients with craniopharyngioma on final pathology and postoperative panhypopituitarism in addition to adjusting for sex, age at presentation, and duration of imaging follow-up in our statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, normative data such as the Bolton standards are based on a homogenous white population. The applicability of this normative data to other ethnic populations has been questioned in numerous studies . As a result, this normative data is not an appropriate control group for our heterogeneous population.…”
Section: Discussionmentioning
confidence: 99%
“…A balanced facial profile is also one of the main objectives of orthodontic treatment, especially the position of upper and lower lip and the nasal relationship of lip and chin. 5 Zhao et al 8 compared the Bolton standards of Chinese and Caucasians at the age of 13; they reported that the Chinese subjects presented a convex facial profile with a less prominent nose and chin. Hwang et al 17 reported that the Korean laypersons preferred more concave profiles but the White respondents preferred more convex profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the structure of the bone/dental and soft tissue profile in the Chinese are more protrusive in comparison with the pattern for the Caucasian. 7 , 8 Given this, it is common for the Chinese to seek orthodontic treatment to improve their facial profile and reduce the protrusion of anterior teeth. An ideal beauty profile is of great importance in orthodontic treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation